The role of the shortened dental arch concept in the management of reduced dentitions - Shaheen, Zakir Ahmed; Rehana, Zinat; Khan, Mohammad Jongish (Journal of Dhaka National Medical College & Hospital, 2015)
Current research indicates that a more biological approach to dental care is required to cope with current trends in adult health and to make more efficient use of ever dwindling public financial resources. This paper describes the role of the shortened dental arch concept (SDA) in the management of reduced dentitions, including criteria for its application, possible indications and contraindications, and presents a review of research supporting SDA. In light of recent research, it is suggested that SDA will be of increasing importance as a treatment philosophy for the future elderly. J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 61-64